2010
DOI: 10.1002/eji.200940157
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐infiltrating IL‐17‐producing γδ T cells support the progression of tumor by promoting angiogenesis

Abstract: Based on the evidence that IL-17 is a key cytokine involved in various inflammatory diseases, we explored the critical role of IL-17-producing cd T cells for tumor development in tumor-bearing mouse model. IL-17 À/À mice exhibited a significant reduction of tumor growth, concomitantly with the decrease of vascular density at lesion area, indicating a pro-tumor property of IL-17. Among tumor-infiltrating lymphocytes (TIL), cd T cells were the major cellular source of IL-17. Analysis of TCR repertoires in TIL-cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
190
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(204 citation statements)
references
References 48 publications
(101 reference statements)
4
190
0
Order By: Relevance
“…Similarly, a recent report on colorectal cancer showed a positive correlation between clinopathological parameters and the infiltration of γδ T cells specifically producing interleukin-17 (IL-17) (17). A tumor-promoting function of γδ T cells was also suggested in murine fibrosarcoma (18) and hepatocellular carcinoma (19) models, in which γδ T cells were the major cellular source of IL-17, which was required for optimal tumor growth in vivo. These data raise the interesting question as to whether distinct functional attributes of γδ T cells, for example differential cytokine production, may associate with markedly different outcomes for tumor growth.…”
Section: Gamma-delta T Cells | Tumor Immunologymentioning
confidence: 84%
See 3 more Smart Citations
“…Similarly, a recent report on colorectal cancer showed a positive correlation between clinopathological parameters and the infiltration of γδ T cells specifically producing interleukin-17 (IL-17) (17). A tumor-promoting function of γδ T cells was also suggested in murine fibrosarcoma (18) and hepatocellular carcinoma (19) models, in which γδ T cells were the major cellular source of IL-17, which was required for optimal tumor growth in vivo. These data raise the interesting question as to whether distinct functional attributes of γδ T cells, for example differential cytokine production, may associate with markedly different outcomes for tumor growth.…”
Section: Gamma-delta T Cells | Tumor Immunologymentioning
confidence: 84%
“…However, these experiments were performed on the murine BALB/c background, where lymphoid organs (both in naïve and tumor-bearing mice) were essentially depleted of IFN-γ-producing γδ T cells (18). By contrast, our study was conducted on the murine C57/Bl6 background, where IFN-γ-producing γδ T cells significantly outnumber their IL-17 (+) counterparts (20).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…19 Moreover, Wakita et al indicated that gd17 cells promote angiogenesis via induction of VEGF secretion. 25 As gd17 cells may exert antitumor functions, [5][6][7]26 we decided to directly investigate the role of gd T cells in our model. Their pro-tumor properties were evidenced by the significant delay in metastasis incidence in Ret mice lacking gd T cells.…”
Section: Discussionmentioning
confidence: 99%